Immigration-Related Trauma Associated With Metabolic Risk and Cognition in Hispanic and Latino Immigrant Populations. (17th December 2021) - Diminich, Erica; Ajrouch, Kristine; Antonucci, Toni; Clouston, Sean; Vega, Irving; Zahodne, Laura; Webster, Noah; Gonzalez, Richard
Abstract: Recent immigrant and undocumented Hispanic/Latino adults in the United States (U.S.) are an underserved segment of the aging population. In this cross-sectional pilot study, we examined associations between self-reported stressors metabolic syndrome, emotional reactivity, and cognitive functioning in a heterogenous sample (N=80) of Hispanic/Latino adults (43.8% Central America; 43.8% South America; 7.5% Caribbean; mean years in the U.S.=18.1, SD=12.8). Participants (Meducation=10.2 years, SD=5.34; Mage=48.6 years, SD=12.3) underwent blood draw, anthropometrics and NIH-toolbox cognitive and behavioral measures. Linear regressions indicated that, elevated glucose was inversely associated with working memory (r=-.30), whereas higher HDL and controlled glucose were associated with better episodic memory (r=.27) and executive functioning (r=.32). Results further revealed associations between immigration-related trauma and elevated posttraumatic stress symptomatology. Implications for mental health and early detection of modifiable risk factors to promote healthy aging in vulnerable Hispanic/Latino immigrant populations are discussed.